2022
DOI: 10.3390/su14159562
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Isolates from Greek Sites and Their Efficacy in Degrading Petroleum

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a major organic pollutant, not only because they do not self-degenerate but also because they accumulate in the food chain and give rise to serious repercussions in terms of biodiversity sustainability. Petroleum-degrading bacteria have long been used as a promising solution in the effort to biodegrade crude oil. In this study, new isolates from specific Greek environments displaying various levels of crude oil contamination, as well as isolates belonging to the ATHU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The application of a consortium resulted in the highest PCB-209 removal potential [ 29 ]. Another study showed that consortia and individual strains had similar crude oil-degrading capacities [ 11 ]. Moreover, [ 37 ] reported that the oil biodegradation efficiency of single strains and consortia ( Actinotalea ferrariae , Arthrobacter ginsengisoli , Dietzia cinnamea , Dietzia papillomatosis , and Pseudomonas songnenensis ) was similar, and that the REs of bioaugmented and non-bioaugmented sets in an oil-saturated desert soil after a 6-month experiment were also similar, exhibiting similar predominant bacterial species, e.g., Ar.…”
Section: Obtaining Microorganism Degraders: Sources and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of a consortium resulted in the highest PCB-209 removal potential [ 29 ]. Another study showed that consortia and individual strains had similar crude oil-degrading capacities [ 11 ]. Moreover, [ 37 ] reported that the oil biodegradation efficiency of single strains and consortia ( Actinotalea ferrariae , Arthrobacter ginsengisoli , Dietzia cinnamea , Dietzia papillomatosis , and Pseudomonas songnenensis ) was similar, and that the REs of bioaugmented and non-bioaugmented sets in an oil-saturated desert soil after a 6-month experiment were also similar, exhibiting similar predominant bacterial species, e.g., Ar.…”
Section: Obtaining Microorganism Degraders: Sources and Methodsmentioning
confidence: 99%
“…Bioaugmentation is a site-specific approach. Thus, recent research publications and reviews on bioaugmentation have focused on the following aspects: thermophilic reductive dechlorination [ 4 , 5 ]; the psychrophilic treatment of groundwaters [ 6 ]; microbially induced calcium carbonate precipitation techniques to mitigate the wind-induced erosion of calcareous desert sand [ 7 ]; hydrocarbon biodegradation in freshwater sediments from historically contaminated lakes [ 8 ]; the bacterial remediation of pesticide-polluted soils [ 3 ], emerging trends in the remediation of organic contaminated soils as a whole [ 9 ]; mechanisms of microbial activity in heavy metal removal [ 10 ]; comparisons of autochthonous and allochthonous bioaugmentation [ 11 ]; the stimulation of plant growth in bioaugmented hydroponic systems [ 12 ]; and the bioaugmentation of wastewaters (WWs) with yeast in the presence of antimicrobials [ 13 ], among others.…”
Section: Introductionmentioning
confidence: 99%